Loss of basic lexical knowledge in old age. Issue 4 (27th August 2010) - Wilson, Robert S; Krueger, Kristin R; Boyle, Patricia A; Bennett, David A
Abstract : Background: Basic lexical skills are hypothesised to be relatively preserved in mild dementia, but clinical studies have reported inconsistent results. Methods: More than 400 older Catholic nuns, priests and brothers recruited from groups across the USA completed annual evaluations for up to 15 years, died and underwent brain autopsy. Each clinical evaluation included administration of a 20-item word reading test and a 15-item vocabulary test, which were combined to form a composite measure of word knowledge. In a uniform neuropathological examination, Alzheimer's disease pathology was quantified with a composite index of plaques and tangles, and the presence of gross and microscopic cerebral infarctions and Lewy bodies was recorded. Results: The post-mortem level of Alzheimer's disease neuropathology was linearly related to rate of decline in word knowledge. Decline was nearly fourfold faster at a relatively high level of pathology (75th percentile) compared with a relatively low level (25th percentile). Neocortical (but not nigral or limbic) Lewy bodies and gross (but not microscopic) cerebral infarction were also associated with a more rapid decline in word knowledge. Effects for word reading and vocabulary were similar, except that gross cerebral infarction was associated with accelerated decline in vocabulary, but not in word reading. Conclusion: Common neuropathological changes associated with late-life dementia impair word knowledge in old age, calling into question the use of word knowledge tests to estimate premorbid cognitive ability.